2009
DOI: 10.1093/nar/gkp1025
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of ribosome–mRNA complexes at different translation stages

Abstract: Inhibition of primer extension by ribosome–mRNA complexes (toeprinting) is a proven and powerful technique for studying mechanisms of mRNA translation. Here we have assayed an advanced toeprinting approach that employs fluorescently labeled DNA primers, followed by capillary electrophoresis utilizing standard instruments for sequencing and fragment analysis. We demonstrate that this improved technique is not merely fast and cost-effective, but also brings the primer extension inhibition method up to the next l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 28 publications
4
50
0
Order By: Relevance
“…Compaction of mRNA in the A site probably results in pulling downstream mRNA further into the mRNA channel. This is consistent with protection of two additional nucleotides of 3’ mRNA upon eRF1 binding to the ribosome 16,17 .…”
supporting
confidence: 85%
“…Compaction of mRNA in the A site probably results in pulling downstream mRNA further into the mRNA channel. This is consistent with protection of two additional nucleotides of 3’ mRNA upon eRF1 binding to the ribosome 16,17 .…”
supporting
confidence: 85%
“…We observed toeprints +17 to +19 nt downstream of AUG ( Figure 10C) which is a hallmark of ribosome recruitment to the AUG and stable ribosome-RNA complex formation. Depending on the distribution of fluorescence intensity (+17< +18 > +19) (Shirokikh et al, 2010) we further confirmed that indeed 80S initiation complex was isolated which was formed on XIAP IRES RNA in eIF2 phosphorylation condition ( Figure 10C). The initiation complex can be further purified by sucrose density gradient separation.…”
Section: Formation and Isolation Of Xiap Ires Initiation Complex By Rsupporting
confidence: 72%
“…The assembly efficiency was determined by primer extension inhibition (toeprinting) using fluorescently labeled DNA primers and capillary electrophoresis (Figure 1D) (19,20). …”
Section: Resultsmentioning
confidence: 99%